2020
DOI: 10.1063/5.0022531
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic plasma atomic layer etching of Al2O3 using a fluorine containing plasma and Al(CH3)3

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The ALE process using TMA and SF 6 plasma developed in the same reactor showed an etch rate of approximately 3 Å at 250 °C and 2 Å at 200 °C, while no etching was observed for temperatures below 150 °C, which indicates a strong dependence on the temperature and corroborates the observed transition from AlF 3 ALD to Al 2 O 3 ALE. 55 In addition, it was confirmed that an SF 6 plasma can be used for fluorination of Al 2 O 3 , similar to the use of HF for thermal ALE. Al 2 O 3 films (∼10 nm thick) were exposed to SF 6 plasma and subsequently analyzed by spectroscopic ellipsometry (SE; see Figure S1).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The ALE process using TMA and SF 6 plasma developed in the same reactor showed an etch rate of approximately 3 Å at 250 °C and 2 Å at 200 °C, while no etching was observed for temperatures below 150 °C, which indicates a strong dependence on the temperature and corroborates the observed transition from AlF 3 ALD to Al 2 O 3 ALE. 55 In addition, it was confirmed that an SF 6 plasma can be used for fluorination of Al 2 O 3 , similar to the use of HF for thermal ALE. Al 2 O 3 films (∼10 nm thick) were exposed to SF 6 plasma and subsequently analyzed by spectroscopic ellipsometry (SE; see Figure S1).…”
Section: Resultsmentioning
confidence: 84%
“…Interestingly, the chemistry based on fluorination and TMA dosing can also be used for ALE of Al 2 O 3 at higher substrate temperatures, which was demonstrated using an SF 6 plasma as the reactant in our previous work . The transition between AlF 3 ALD and Al 2 O 3 ALE is governed by the substrate temperature and is believed to depend on the desorption temperature of AlF x (CH 3 ) 2– x species .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations